NONPROFIT, CRIMINAL HUBS AND RENT SEEKING. EVALUATION OF THE CALABRIAN EXPERIENCE - MAGAZZINO, Cosimo (Journal of Environmental Management and Tourism, 2011)
The study concerns rent seeking in the allocation of structural funds for cultural development in the Italian region of Calabria. By statistical analysis the study shows that the variables relating to major cultural sites had no robust significance. Rent seeking variables relating to non profits, criminal hubs and construction interests were statistically significant. This may explain both the fragmentation of the projects and the difference between allocations and payments relating to the allocation of the funds. On the other hand, the presence of major cultural sites is not significant in the allocation of funds to the criminal hubs, likely because this type of projects would be closely controlled by the public authorities in charge of the preservation and valorization of the cultural heritage. The anomalous discrepancy between allocation of funds and payments also may be explained as a rent seeking phenomenon. Finally, discrete choice analysis show that municipal with an academic institution have a 39.5% higher probability of receiving cultural funds; municipal with an airport or a seaport have a 33.9% higher probability to catch some financings; whereas a marginal change in museums is associated with a 19.8% in participation.